Rational use of energy: paths and realisable potential. (4th August 2014) - Schaefer, H.
The limits on achievable energy savings are primarily physical and technological, but there may also be economic, ecological or social constraints. There is no single route to the ideal energy world. Several realistic routes should be taken in parallel so that their respective advantages can be exploited to the full and their disadvantages avoided. Success will depend upon educating individuals in the elementary facts of energy technology.